2008
DOI: 10.1593/neo.08590
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Overexpression of c-IAP2 in EBV-Associated Nasopharyngeal Carcinomas: Critical Role in Resistance to Toll-like Receptor 3-Mediated Apoptosis

Abstract: The oncogenic process leading to nasopharyngeal carcinoma (NPC) requires the combination of genetic and epigenetic alterations, latent infection by the Epstein-Barr virus and local inflammation. A transcriptome analysis of NPC xenografts identified the gene encoding the cellular inhibitor of apoptosis protein 2 (c-IAP2) among the top five most intensely expressed. Consistently, the very high levels of the c-IAP2 protein were detected in 11 of 13 NPC biopsies. RMT 5265, a structural analog of second mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…TLR3 also signals inflammation in normal bronchial and nasopharyngeal epithelial cells that, however, appear insensitive to poly(I:C)-induced apoptosis, even in the presence of Smac mimetic (our unpublished data and Friboulet et al 7 ). Thus, cIAPmediated RIP1 ubiquitination alone is unlikely to explain resistance to TLR3-triggered apoptosis in normal epithelial cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…TLR3 also signals inflammation in normal bronchial and nasopharyngeal epithelial cells that, however, appear insensitive to poly(I:C)-induced apoptosis, even in the presence of Smac mimetic (our unpublished data and Friboulet et al 7 ). Thus, cIAPmediated RIP1 ubiquitination alone is unlikely to explain resistance to TLR3-triggered apoptosis in normal epithelial cells.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, we and others have recently demonstrated that TLR3 can trigger caspase-8-dependent apoptosis in human cancers. [5][6][7] Related to this proapoptotic function, we also found that TLR3 expressed by breast cancer cells is a biomarker for the therapeutic efficacy of dsRNA. 8 Unlike classical death receptors (DRs), TLR3 lacks a death domain (DD) and thus the molecular basis of dsRNA-triggered apoptosis through caspase-8 remains an open question although recent reports indicate that TRIF and RIP1 are required for Poly(I:C) to engage the apoptotic machinery.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…18 IAP family members protect cells from apoptosis by inhibiting caspases and by regulating RIP1 ubiquitination status. 12,13,16,30,31 In addition, IAPs have been implicated in several RIP1-dependent apoptotic triggers (such as stimulation of TNFR1, Fas, or toll-like receptor 3 (TLR3)) [14][15][16]18,[32][33][34] that can also induce necrotic cell death under certain conditions. We found that the IAP antagonist BV6 greatly sensitized L929 cells to TNF-induced necrotic cell death, but not to necrosis induced by poly(I:C) þ IFNb, anti-Fas þ zVADfmk, or H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…siRNA against c-IAP2 (Birc3) was purchased from Gibco-Invitrogen (Stealth Select RNAi TM siRNA, HSS100562, Carlsbad, CA, USA) [50]. Transfection was performed according to the procedure described previously [27,51].…”
Section: Transfectionmentioning
confidence: 99%